PENGARUH SUBSTITUSI TEPUNG WORTEL (Daucus carota L) TERHADAP KUALITAS SENSORIS, FISIK, dan KIMIA CHIFFON CAKE - Cicilia, Sumale E.; Tuju, Thelma D. J.; Ludong, Maya M. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2021)
The purpose of this research was to determine the best substitution of carrot flour and wheat flour in terms of texture, color and taste of the resulting chiffon cake and to analyze the nutritional content of the chiffon cake with the best substitution of carrot flour and wheat flour, it was better than the control. The research was arranged in Completely Randomized Design (CRD), with the substitution treatment of carrot flour and wheat flour. The results for a better chiffon cake according to organoleptic test result are treatment A (30% carrot flour and 70% flour) with the same level of comparison in texture as control, on color is better than control and taste better then control. The results of the analyze of the chemical composition showed 11.43% protein content, 2.42% fiber content, 29.08% water content, 1.69% ash content, 48.16% carbohydrate contentAbstract in English should be written in italic. Word count should not exceed 250 words. Composed of the purpose of researh, methods, results, and conclusion.